(untitled) (The International Research Journal of Management Science, 2017)
The purpose of this paper is to examine the association between Nepalese enterprises’ choice of strategic position and their cost behavior. The research design adopted in this study consists of descriptive and causal-comparative research designs to deal with the various issues raised in this study. Secondary data has been used for this study which was collected from annual audit report of concerned organization of manufacturing and hotel industrities from fiscal year 2000/01 to 2014/15. Descriptive statistics, correlation analysis, and regression analysis are different statistical tool that has been used for this study. Cost stickiness of the enterprises pursuing a differentiation strategy is higher than that of following a cost leadership strategy. This paper contributes to the literature on cost management by explaining how strategic positioning affects firms’ cost behavior using the framework of asymmetric cost behavior.